2021
DOI: 10.3390/e23050559
|View full text |Cite
|
Sign up to set email alerts
|

The Vegetation–Climate System Complexity through Recurrence Analysis

Abstract: Multiple studies revealed that pasture grasslands are a time-varying complex ecological system. Climate variables regulate vegetation growing, being precipitation and temperature the most critical driver factors. This work aims to assess the response of two different Vegetation Indices (VIs) to the temporal dynamics of temperature and precipitation in a semiarid area. Two Mediterranean grasslands zones situated in the center of Spain were selected to accomplish this goal. Correlations and cross-correlations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…Vegetation indexes are an effective indicator of grassland cover. Their response is highly interrelated with climate and agricultural conditions [62,63]. In fact, multiple authors [64,65] have reported a clear relationship between grasslands vegetation and water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation indexes are an effective indicator of grassland cover. Their response is highly interrelated with climate and agricultural conditions [62,63]. In fact, multiple authors [64,65] have reported a clear relationship between grasslands vegetation and water availability.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, depending on the goal of the study, such as differentiating soil from biomass or differentiating the presence of perennial or annual plants, soil-adjusted VI or other indices may be better suited. The selection of best fit should be made on a case basis, especially in the most extreme areas (Almeida-Ñauñay et al, 2021;Fern et al, 2018). Nevertheless, NDVI has been proven well suited to assess general cover monitoring, regardless of soil or vegetation variations (Al-Bakri and Suleiman, 2004;Klisch and Atzberger, 2016;Peters et al, 2002;Ünal et al, 2014;Wallace et al, 2006;Yagci et al, 2014).…”
Section: Vegetation Indicesmentioning
confidence: 99%